P252 COPD readmission rates: turning the tide. (12th November 2019) - Sobala, RE; Conroy, KP; Lane, ND; Bourke, SC
Abstract : Introduction: Readmission rates post COPD exacerbation are increasing. In 2014 the National COPD Audit showed 90 day all- cause readmission rates had risen, from 31% in 2003, to 43%. We assessed whether by addressing key modifiable factors we could decrease readmission rates and turn the tide. Method: The areas identified were: optimising COPD management including vaccination, hospital initiated smoking cessation, pulmonary rehabilitation and home ventilation, identification and treatment of cardiac and mental health comorbidities, identifying re-exacerbations (10–14 day bacterial surge), and promoting healthy nutrition and physical activity. Pre-discharge usual inpatient teams were asked to address the key elements above. We aimed to undertake a structured review of all patients within 14 days of discharge. Patients discharged under the care of the Supported Discharge Service were reviewed at home. For other patients, slots were created within existing clinics and non-attenders were then offered a telephone review. Results: 54 index admissions were collected prior to initiating the review and compared to 58 admissions post review implementation. Demographics of both groups were similar with a mean PEARL score of 4. Pre-intervention, 24 patients (44.4%) were readmitted within 90 days of discharge and 19 patients (35.2%) were readmitted within 30 days. Post review implementation 24 patients (41.4%) were readmitted within 90 days of discharge and 15 patients (25.9%) were readmitted within 30 days. The most common readmission reason was IECOPD. Of the 58 patients eligible for review, 38 patients attended. Non-attendance was more often due to lack of arrangements being made (n= 17) than failure to attend (n= 3). 90 day readmission rates in those reviewed was 14 patients (36.8%) compared to 10 patients (50%) in those not seen. Discussion: Due to a mean PEARL score of 4, our patient demographic had a high likelihood of readmission within 90 days. Numerically there were fewer 90 day readmissions for patients who attended a structured review, however this did not achieve statistical significance. The study was under-powered. Whilst this was a small project, hospital admissions for COPD are rising; the potential benefits to patients and the NHS are large.